The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1807-3107bor-2016.vol30.0013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea as a protective measure against dental erosion in coronary dentine

Abstract: Effect of green tea as a protective measure against dental erosion in coronary dentine Abstract: The aim of this study was to evaluate the effect of green tea as a protective measure on eroded dentin. Disks of human coronary dentin were selected based on surface hardness and randomly assigned to 3 groups (n = 10): DW -distilled water, CHX -0.2% chlorhexidine digluconate, and GT -green tea. The disks were allowed to acquire pellicle for 2 hours and were then subjected to 3 cycles per day of demineralization (C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
1
29
0
7
Order By: Relevance
“…Surface hardness loss (% SHL), wear and surface roughness analysis were measured. The results of the study showed no significant difference between chlorhexidine and green tea group, however there was a significant difference between green tea and distilled water group 25 .…”
Section: Introductionmentioning
confidence: 70%
“…Surface hardness loss (% SHL), wear and surface roughness analysis were measured. The results of the study showed no significant difference between chlorhexidine and green tea group, however there was a significant difference between green tea and distilled water group 25 .…”
Section: Introductionmentioning
confidence: 70%
“…36 Green tea has many beneficial properties for the treatment of cardiac diseases and obesity. 16,17 Anticarcinogenic properties of green tea have also been confirmed. [36][37][38] Since EGCG is the most active component of green tea extract, 39 it was used as the green tea extract in our study.…”
Section: Discussionmentioning
confidence: 78%
“…The anticariogenic mechanisms of green tea have been partly understood. [16][17][18] Duration of exposure of tooth structure to green tea affects its cariostatic efficacy. Thus, to benefit from its cariostatic effects, green tea must be used in a form with maximum durability on the tooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in surface microhardness values after immersion in green tea solution reveals an improvement in the demineralized structure of eroded dentin. 22 After immersion in green tea, there are obvious deposits on the dentin surface and conversion into a more organized, feature is detected on SEM evaluation. 2 Preservation of dentin matrix by MMP inhibition might be another probable explanation for these observations.…”
Section: Discussionmentioning
confidence: 99%